Compatibility of intravenous acetaminophen with morphine, fentanyl and ketamine in acute pediatric pain setting. Issue 7 (24th April 2022) - O'Loughlin, Edmond; Peng, Yan Ghee; Cheaib, Angela; Chan, Matthew T. V.; Williams, Robin
Abstract: Background: Intravenous acetaminophen and opioid analgesics are routinely given concurrently to children after major surgery, where intravenous access can be limited. There is limited information about the compatibility of acetaminophen with opioid analgesics and ketamine in concentrations commonly used in pediatric setting. Aims: We aimed to determine the physical and chemical compatibility in mixtures of intravenous acetaminophen 10 mg/mL with morphine (0.025, 0.05, 0.1, 0.2, 1, and 2 mg/ml), fentanyl (0.5, 0.75, 1, 1.5, 2, and 5 mcg/ml) and ketamine (0.01, 0.1, 0.5, 1, 1.5, and 3 mg/ml). Methods: Acetaminophen was mixed with all 18 solutions and was examined at time 0, 15, 30, and 60 min. In Phase one of the study, we used a colorimetric method to assess preliminary feasibility and acetaminophen recovery. In Phase two study, we used high‐performance liquid chromatography to evaluate the recovery of all components of the mixtures. Results: All solutions tested, for both acetaminophen and the three analgesics, had more than 90% of the drug recovery, up to 60 min after mixing. Conclusion: Our data demonstrated the stability of acetaminophen, in combination with fentanyl, morphine, and ketamine at clinical concentrations used in acute pediatric pain setting.